Moving on Up Now? A Meta-Analysis of the Associations Between Job Insecurity and Career-Related Outcomes - Lena Låstad; Jacobus Pienaar; Katharina Näswall; Anne Richter; Johnny Hellgren; Magnus Sverke (Scandinavian Journal of Work and Organizational Psychology)
Job insecurity constitutes uncertainty about the future of the current job. Such uncertainty is expected to impact attitudes and behaviors about one’s work and career and how it will progress. The aim of the present study is to meta-analytically consolidate research on the associations between job insecurity and career-related outcomes. A further aim of the study is to explore two methodological moderators: study design (cross-sectional vs. longitudinal) and type of job insecurity measure (cognitive, affective, or combined). Based on a sample of 237 primary studies, our main results show that job insecurity was positively related to occupational and organizational turnover intention, job search behaviors, and knowledge hiding, and negatively related with career satisfaction, career opportunities, employability, and proactive skill development. In terms of the moderators, the associations were generally stronger in cross-sectional studies compared to longitudinal studies, while the impact of the type of job insecurity measure used was mixed. While our results inform research on job insecurity and career-related outcomes, more studies with a longitudinal design are needed on this research topic. Future research should also further examine how different types of job insecurity measures – cognitive, affective, or combined – are associated with career-related outcomes.